PENGARUH RASIO-RASIO KEUANGAN TERHADAP DIVIDEND PAYOUT RATIO (DPR) (Studi Pada Perusahaan Yang Listing Di BEI Tahun 2009 – 2011) - Septi Rahayuningtyas (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
The purpose of this research is to determine the effect of independent variables represented by the current ratio (CR), Return on Equity (ROE), Total Assets Turn Over (TATO), Debt to Equity Ratio (DER), and Price Earnings Ratio (PER) both simultaneous or partially has influence on the dependent variable is Dividend Payout Ratio (DPR).This research is explanatory research. The research population is companies that listed on the time Stock Exchange in 2009 - 2011 by using ICMD data in 2009 - 2012 consist of 14 samples of companies that have met certain criteria that have been adjusted. The method of analysis in this research is linear multiple regression.The analysis results of this research are the five independent variables which are represented by the current ratio (CR), Return on Equity (ROE), Total Assets Turn Over (TATO), Debt to Equity Ratio (DER), and Price Earnings Ratio (PER) simultaneously have significant effect on the Dividend Payout Ratio (DPR). While, partially, only PER variable that has significant influence on Dividend Payout Ratio (DPR). Keywords: Financial Ratios, Dividend Payout Ratio (DPR) ABSTRAK Tujuan penelitian ini yaitu untuk mengetahui pengaruh variabel bebas yang diwakili oleh Current Ratio (CR), Return On Equity (ROE), Total Assets Turn Over (TATO), Debt to Equity Ratio (DER), dan Price Earning Ratio (PER) baik secara simultan maupun secara parsial terhadap variabel terikat yaitu Dividend Payout Ratio (DPR). Jenis penelitian ini adalah explanatory research. Populasi penelitian ini adalah perusahaan yang listing di BEI pada periode penelitian 2009 – 2011 dengan menggunakan ICMD 2009 - 2012 dan didapat 14 sampel perusahaan yang telah memenuhi kriteria tertentu yang telah disesuaikan. Metode analisa dalam penelitian ini adalah regresi linear bergandaHasil analisis dari penelitian ini adalah kelima variabel bebas yang diwakili oleh Current Ratio (CR), Return On Equity (ROE), Total Assets Turn Over (TATO), Debt to Equity Ratio (DER), dan Price Earning Ratio (PER) secara simultan berpengaruh signifikan terhadap Dividend Payout Ratio (DPR). Sedangkan secara parsial hanya variabel PER yang berpengaruh signifikan terhadap Dividend Payout Ratio (DPR). Kata Kunci: Rasio keuangan, Dividend Payout Ratio (DPR)